Global Aggregated Ranking of HEIs: Russian Footprint - V. A. Bolotov; G. N. Motova; V. G. Navodnov (Высшее образование в России)
The paper suggests a new approach to performance evaluation of universities in Russia and worldwide based on aggregation of the results of ten global rankings and the Database of External Quality Assurance Results (DEQAR). The method of league analysis (MetALeague) allows the authors to integrate the diverse results of ranking and evaluation regardless of considerable variations in ranking methodology and indicators. As a result of MetALeague integration, the Global Aggregated Ranking of higher education institutions has been made. The paper analyses the global rankings and the position of Russian HEIs in these rankings. The authors have also analyzed the positions of countries based on the number of HEIs included in the Global Aggregated Ranking. The due consideration of research results, according to the authors, can propel the leading Russian universities to higher positions in the global educational environment.